P052: Who are the super-users of the emergency department?. (May 2020) - North, R.; Savage, D.; VanderBurgh, D.; McKay, G.; McMillan, C.; Jefferies, A.; Piper, B.; Stonebridge, R.
Abstract : Introduction: All emergency departments (EDs) across Canada can identify a group of high frequency users, which are typically defined in the literature as eight to ten visits per year. Although frequent users of the ED are well-studied in the literature, there is little published in terms of identifying the "super-user" group who present to the ED much more often than 10 visits per year. Faced with multiple co-morbidities and a high mortality rate, the ED is often the most appropriate environment to manage this population. In order to inform future initiatives to improve health outcomes, we aimed to identify the specific characteristics of this super-user group. Methods: A retrospective chart review was conducted using the electronic medical record from the Thunder Bay Regional Health Sciences Centre to identify patients who had at least 25 visits in the year 2017. A total of 75 patients presented to the ED greater than 25 times in 2017. The following data was then collected on each individual patient: demographic characteristics including age, gender, address, access to a primary care provider. In addition, we collected date, time, diagnoses at each visit, admission rate and surgical interventions. Results: Our preliminary results reveal this population presents to the ED on average 32 times per year. The population is 53% male. Most have a private address and half have a primary care provider for all 2017 with one quarter having a primary care provider for part of the year. The percentage of visits for infections was 30%, mental health and addictions presentations comprised 28% of the visits, with gastrointestinal and cardiac visits comprising a total 22% of the visits. Approximately 7% of visits required admission to hospital, and the average length of stay was 5 days. Conclusion: Super-users of the ED are a unique population that are typically well connected with primary care and have a very low admission and surgical rate. The most common reasons for visit are infections and mental health and addictions. The next steps include collecting mortality data. This data should be used to inform ED and community initiatives aimed at improved health outcomes for this population.